The Perceptions of Local Community's About Diversity of Mangrove Ecological Potential for Ecotourism Development in the South Coast of Lombok Island, Indonesia - Lalu Raftha Patech; Kumala Ratna Dewi; Zulhalifah Zulhalifah; Abdul Syukur; Jamaluddin Jamaluddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
The utilization of the coastal environment is still dominated by-products and has not yet switched to ecosystem service products, such as the use of mangrove ecosystems as ecotourism. This study aims to assess the local community's perception of the potential diversity that becomes an object for the community's economy. The research method uses surveys, observations, and interviews for social data, while the ecological data use transect and quadratic methods. Furthermore, data analysis used descriptive statistics. In addition, ecological data were analyzed using density (Ki), relative frequency (FR), diversity (H') of mangroves, and ecological indexes (Diversity (H'), Evenness (E), Dominance (D)). The results of the study found six mangrove species, ten echinoderm species, and thirteen bivalves. The highest diversity index (H') was in Poton Bako 1.80 and the Evenness index ranged from 0.80 Ã¢â¬â 0.98 with a stable category. Biota relative dominance the association index of echinoderms is high 0.79Ã¢â¬â0.11. Meanwhile, the bivalves Dominance index of 0.03-0.11 was low. In addition, local community's perception of mangrove conservation for ecotourism, 63% of the community stated, 7% is not possible and 30% is not. The feasible value of mangrove development is 62%, 17% is not feasible and 21% does not know. The priority developed by Eduwisata is 48%, Bird Watching is 20% and Tracking is 32%. The conclusion is that the choice of using mangrove ecosystem services can be developed as a policy in overcoming economic threats and the vulnerability of marine biota as well as solutions for local communities.